Ultimate conductivity performance in metallic nanowire networks. Issue 30 (14th July 2015) - Gomes da Rocha, Claudia; Manning, Hugh G.; O'Callaghan, Colin; Ritter, Carlos; Bellew, Allen T.; Boland, John J.; Ferreira, Mauro S.
Abstract : In this work, we introduce a combined experimental and computational approach to describe the conductivity of metallic nanowire networks. Abstract : In this work, we introduce a combined experimental and computational approach to describe the conductivity of metallic nanowire networks. Due to their highly disordered nature, these materials are typically described by simplified models in which network junctions control the overall conductivity. Here, we introduce a combined experimental and simulation approach that involves a wire-by-wire junction-by-junction simulation of an actual network. Rather than dealing with computer-generated networks, we use a computational approach that captures the precise spatial distribution of wires from an SEM analysis of a real network. In this way, we fully account for all geometric aspects of the network, i.e. for the properties of the junctions and wire segments. Our model predicts characteristic junction resistances that are smaller than those found by earlier simplified models. The model outputs characteristic values that depend on the detailed connectivity of the network, which can be used to compare the performance of different networks and to predict the optimum performance of any network and its scope for improvement.